Requirements analysis for technical interoperability driven by mission engineering - Lana, Cristiane Aparecida (2020)
Context: Systems-of-Systems (SoS) have drawn the interest of both industry and academia owing to the continuous growth of business applications. Constituent systems (CSs) can redirect their resources and capabilities towards achieving the SoS mission with new and enhanced functionalities, which would not be feasible by a single CS working independently. The mission is at the core of SoS design, which build upon the reliable analysis of technical interoperability to obtain cohesive SoS bevavior. SoS exhibit emergent behavior, resultant from the interoperation of their CSs, leading to emergence of needs, capabilities, and requirements at runtime. Aims: this research aims at the development of a substantive theory supporting the analysis of technical interoperability requirements drive by mission for the design and development of SoS. Method: The research was guided by the grounded theory tailored for the construction of substantive theories based on empirical data systematically analyzed and compared with the literature. The data were collected through of practitioners and researchers developing industrial projects in Brazil, USA, Germany, and Spain, from November/2017 to November/2019, using a survey, interviews. Data were analyzed with the content analysis method by the Atlas/Ti 8.0. Results: We analyzed 51 survey responses and 17 interviews for designing a new theoretical framework, named ATLANTA. It is comprised eleven categories and five sets of knowledge that may assist the analyses of technical interoperability requirements bounded time and space, and of the business value towards monitoring changes and perspectives for future evolutionary procedures of the SoS development. ATLANTA covers and does not limit to (i) the SoS modeling and design through of the Triplet model, which integrate mission, requirements, and architectural requirements specification, (ii) the situational analysis for SoS enabling identification and analysis of mission based on OKR, and (iii) the specification of technical interoperability requirements derivative from mission adopting specific transformations properties and quality models at design time and runtime. Conclusions: ATLANTA promotes a better understanding of the technical interoperability requirements influence on the SoS mission behavior and shows the importance of enterprise analysis to the SoS level during its lifecycle at design time and runtime. The particular focus on practitioners bridges the state-of-the-art and state-of-the-practice. Mission engineering crosscuts analysis, design, and development of SoS, reflecting on the emergent behavior at runtime. Thereby, this theory is intended to support researchers and practitioners in analysis and maintaining technical interoperability requirements and definition/specification/modeling of mission SoS, through a strategical and agile approach of the industrial environment over time.